2016
DOI: 10.1515/heem-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Transport Beyond the Surf Zone Under Waves and Currents of the Non-Tidal Sea: Lubiatowo (Poland) Case Study

Abstract: The paper deals with the sandy coastal zone at Lubiatowo in Poland (the south Baltic Sea). The study comprises experimental and theoretical investigations of hydrodynamic and lithodynamic processes in the coastal region located close to the seaward boundary of the surf zone and beyond the surf zone. The analysis is based on field data collected at the IBW PAN Coastal Research Station in Lubiatowo. The data consist of wind velocity reconstructed from the long-term wave climate, deep-water wave buoy records and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recently, Ostrowski and Stella (2016) have presented a study concerning sediment transport beyond the surf zone under waves and wind-induced currents of the non-tidal sea. Their investigations were based on wave data collected at CRS Lubiatowo and a long-term reconstruction of the regional wind climate.…”
Section: Mechanics-based Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ostrowski and Stella (2016) have presented a study concerning sediment transport beyond the surf zone under waves and wind-induced currents of the non-tidal sea. Their investigations were based on wave data collected at CRS Lubiatowo and a long-term reconstruction of the regional wind climate.…”
Section: Mechanics-based Modellingmentioning
confidence: 99%
“…Nielsen 2009). This effect was taken into account in the study of Ostrowski and Stella (2016). The modelling results showed that the highest bed shear stresses are generated by the joint action of waves and the wind-driven current.…”
Section: Mechanics-based Modellingmentioning
confidence: 99%